Prevalence of Cardiovascular Dysfunction and its Association with Outcomes in Patients with Acute Pancreatitis - Mohammad Hanif, Azhar Saeed, Salman Khan, Saadia Zainab, Amanullah Khokhar, Muhammad Shuaib, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Acute pancreatitis is a rapid progressive abdominal inflammatory disease with acute onset in clinics which turns into severe acute pancreatitis. In approximately 20% of patients characterized by different parameters such as gland flaky necrosis, multiple organ dysfunction syndrome (MODS), inflammatory cell infiltration in large number, and hemorrhage. Electrocardiography and electromyography variations are the common cardiac failure in patients with acute pancreatitis. Elevated cardiac enzymes could be other factors for cardiac failure with acute pancreatitis. The present study aimed to assess the prevalence of cardiovascular dysfunction and its association in patients with acute pancreatitis. Methodology: This cross-sectional study was carried out on 120 acute appendicitis patients in the department of Gastroenterology at Northwest General Hospital & Research Centre, Hayatabad Peshawar for the duration of six months from June 2021 to November 2021. All the patients who met the inclusion criteria were enrolled. Echocardiography and CK-MB (creatine phosphokinase isoenzyme) was measured for evaluating myocardial function after admission. All the patients underwent physical, clinical, and laboratory examination. The findings of Electrocardiography (ECG) were recorded. Acute appendicitis severity, duration of hospital stay, infection, computed tomography severity index (CTSI), and mortality were different outcomes. Results: Of the total 120 patients, about 83 (69.2%) were males and 37 (30.8%) were females. The overall mean age was 37.84±12.46 years. Out of 120 acute pancreatitis patients, the prevalence of gallstone disease, organic failure, respiratory failure, acute kidney failure, and cardiovascular dysfunction was 51 (43.3%), 47 (39.2%), 37 (30.8%), 19 (15.8%), and 9 (7.5%) respectively. Elevated CK-MB and ECG changes were seen in 32 (26.7%) and 42 (35%) respectively. The ECG variations and elevated CK-MB were related with severity of acute pancreatitis (p<0.05), duration of hospital (OR: 18.9 ± 10.6 vs. 11.7 ± 6.8, p = 0.005), CTSI (6.9 ± 3.1 vs. 4.7 ± 2.9, p = 0.001), increased necrosis (2.34, 95%CI= 0.3-11.8, p=0.011), and mortality (OR= 5.46, 95% CI= 1.2-34.9, p=0.05). The incidence of Left ventricular systolic dysfunction (LVEF) and left ventricular diastolic dysfunction (LVDD) was 15 (12.5%) and 31 (25.8%) respectively. Conclusion: The present study found that elevated CK-MB were significantly associated with higher CTSI, Prolonged hospital stay, severity of acute pancreatitis, LVDD, increased necrosis, and mortality. CK-MB increased levels have been reported as an indicator for cardiac failure and acute pancreatitis. There was a significant association between increased CK-MB levels and cardiovascular organ failure, pancreatic necrosis, and left ventricular diastolic dysfunction. Keywords: Cardiovascular dysfunction, Acute pancreatitis, Outcomes